Non‐reproducible signals of adaptation to elevation between open and understorey microhabitats in snapdragon plants. (20th December 2021) - Gibert, Anaïs; Marin, Sara; Mouginot, Pierick; Archambeau, Juliette; Illes, Morgane; Ollivier, Gabriel; Gandara, Alice; Pujol, Benoit
Abstract: Experimental studies on local adaptation rarely investigate how different environmental variables might modify signals of adaptation or maladaptation. In plant common garden experiments, signals of adaptation or maladaptation to elevation are usually investigated in open habitats under full light. However, most plants inhabit heterogeneous habitats where environmental conditions differ. Understorey microhabitats are common and differ in terms of tree shade, temperature, water availability, microbiota, allelochemicals etc. Germination is a fitness‐related trait of major importance for the adaptation of plants to contrasted climate conditions. It is affected by shade in snapdragon plants ( Antirrhinum majus ) and many other plant species. Here, we tested for the reproducibility of signals extrapolated from germination results between open and understorey microhabitats in two parapatric snapdragon plant subspecies ( A. m .  striatum and A. m .  pseudomajus ) characterized by a similar elevation range by using common garden experiments at different elevations. Signals observed under one microhabitat systematically differed in the other. Most scenarios could be inferred, with signals either shifting, appearing or disappearing between different environments. Our findings imply that caution should be taken when extrapolating the evolutionary significance of these types of experimental signals because they are not stable from one local environmental condition to the next. Forecasting the ability of plants to adapt to environmental changes based on common garden and reciprocal transplant experiments must account for the multivariate nature of the environment. Abstract : Potential signals of adaptation to elevation obtained in snapdragon plants ( Antirrhinum majus ) common garden experiments differ between microhabitats (open habitat and understorey), thereby suggesting a lack of reproducibility of adaptation signals obtained in simplified experimental environments.